Dabigatran dual therapy with ticagrelor or clopidogrel after percutaneous coronary intervention in atrial fibrillation patients with or without acute coronary syndrome: a subgroup analysis from the RE-DUAL PCI trial - Oldgren, Jonas; Steg, Philippe Gabriel; Hohnloser, Stefan H.; Lip, Gregory Y. H.; Kimura, Takeshi; Nordaby, Matias; Brückmann, Martina; Kleine, Eva; ten Berg, Jurrien M.; Bhatt, Deepak L.; Cannon, Christopher P. (European heart journal, 2019)
Aims: After percutaneous coronary intervention (PCI) in patients with atrial fibrillation, safety and efficacy with dabigatran dual therapy were evaluated in pre-specified subgroups of patients undergoing PCI due to acute coronary syndrome (ACS) or elective PCI, and those receiving ticagrelor or clopidogrel treatment. Methods and results: In the RE-DUAL PCI trial, 2725 patients were randomized to dabigatran 110 mg or 150 mg with P2Y12 inhibitor, or warfarin with P2Y12 inhibitor and aspirin. Mean follow-up was 14 months, 50.5% had ACS, and 12% received ticagrelor. The risk of the primary endpoint, major or clinically relevant non-major bleeding event, was reduced with both dabigatran dual therapies vs. warfarin triple therapy in patients with ACS [hazard ratio (95% confidence interval), 0.47 (0.35–0.63) for 110 mg and 0.67 (0.50–0.90) for 150 mg]; elective PCI [0.57 (0.43–0.76) for 110 mg and 0.76 (0.56–1.03) for 150 mg]; receiving ticagrelor [0.46 (0.28–0.76) for 110 mg and 0.59 (0.34–1.04) for 150 mg]; or clopidogrel [0.51 (0.41–0.64) for 110 mg and 0.73 (0.58–0.91) for 150 mg], all interaction P-values >0.10. Overall, dabigatran dual therapy was comparable to warfarin triple therapy for the composite endpoint of death, myocardial infarction, stroke, systemic embolism, or unplanned revascularization, with minor variations across the subgroups, all interaction P-values >0.10. Conclusion: The benefits of both dabigatran 110 mg and 150 mg dual therapy compared with warfarin triple therapy in reducing bleeding risks were consistent across subgroups of patients with or without ACS, and patients treated with ticagrelor or clopidogrel.